A Roadmap towards the Decarbonization of Shipping: A Participatory Approach in Cyprus - Nisiforou, Olympia A.; Shakou, Louisa Marie; Magou, Afroditi; Charalambides, Alexandros G. (My University, 2022)
Greenhouse gas (GHG) emissions from human activities are driving climate change and are currently at their highest levels in history. The international community, through the United Nations process, places great emphasis on the decarbonisation of our economies across all sectors. GHG emissions from maritime transport, even if considered the most carbon efficient method of transportation, are projected to increase if no action is taken to decarbonise, and thus pressure has extended to the maritime sector to contribute to the significant GHG emission cuts necessary. The paths by which the maritime sector can contribute to the achievement of the international target of GHG reduction by 2050 are still being determined, but numerous promising options exist. This paper aims to provide an overview of action towards decarbonisation by the international maritime sector, and to assess how Cyprus, an important flag state, can contribute to decarbonisation efforts. A participatory approach was used, through implementation of the EIT Climate-KIC’s Deep Demonstrations methodology, as part of the ‘ Zero-Net Emissions, Resilient Maritime Hubs in Cyprus’ project. The results were used to identify a portfolio of actions related to policy and regulatory development, education and re-skilling, technological development, and operation optimisation, which can support the decarbonisation of the maritime sector in Cyprus.
Keywords: Maritime; Sustainability; Decarbonization; Stakeholders; Shipping